Sulaiman B. Kadir V. Public Prosecutor: Punishable with Death or Imprisonment for Life - Mohan, S. Chandra (Journal of Malaysian and Comparative Law, 2018)
Criminal Law: Punishable with Death or Imprisonment for Life